The E-Subgroup Pentatricopeptide Repeat Protein Family in Arabidopsis thaliana and Confirmation of the Responsiveness PPR96 to Abiotic Stresses - Liu, Jia-Ming; Zhao, Juan-Ying; Lu, Pan-Pan; Chen, Ming; Guo, Chang-Hong; Xu, Zhao-Shi; Ma, You-Zhi (Frontiers in Plant Science, 2016)
Pentatricopeptide repeat (PPR) proteins are extensive in all eukaryotes. Their functions remain as yet largely unknown. Mining potential stress responsive PPRs, and checking whether known PPR editing factors are affected in the stress treatments. It is beneficial to elucidate the regulation mechanism of PPRs involved in biotic and abiotic stress. Here, we explored the characteristics and origin of the 105 E subgroup PPRs in Arabidopsis thaliana. Phylogenetic analysis categorized the E subgroup PPRs into five discrete groups (Cluster I to V), and they may have a common origin in both A. thaliana and rice. An in silico expression analysis of the 105 E subgroup PPRs in A. thaliana was performed using available microarray data. 34 PPRs were differentially expressed during A. thaliana seed imbibition, seed development stage(s), and flowers development processes. To explore potential stress responsive PPRs, differential expression of 92 PPRs was observed in A. thaliana seedlings subjected to different abiotic stresses. qPCR data of E subgroup PPRs under stress conditions revealed that the expression of 5 PPRs was responsive to abiotic stresses. In addition, PPR96 is involved in plant responses to salt, abscisic acid (ABA), and oxidative stress. The T-DNA insertion mutation inactivating PPR96 expression results in plant insensitivity to salt, ABA, and oxidative stress. The PPR96 protein is localized in the mitochondria, and altered transcription levels of several stress-responsive genes under abiotic stress treatments. Our results suggest that PPR96 may important function in a role connecting the regulation of oxidative respiration and environmental responses in A. thaliana.